Expressed Willingness and Awareness of Students towards Climate Change in Lahore, Pakistan - Khadija Gulraiz; Aabgeen Ali (CV. Literasi Indonesia, 2021)
Global climate change is one of the most significant threats to our generation, the fundamentals of the issue lie in the fact that the anthropogenic contribution of greenhouse gases is changing the global climate at a rapid rate causing immense warming trends and displaced cold weather. This study examined the awareness levels of college/university students on climate change and their willingness to mitigate the effects of climate change. 69 students from Lahore’s different public and private sector universities were asked to fill out a survey questionnaire form online and were questioned on their attitudes about climate change and their willingness to take action to mitigate its effects.